Calcium Stores in Vertebrate Photoreceptors - Križaj, David (2012)
This review lays out the emerging evidence for the fundamental role of Ca(2+) stores and store-operated channels in the Ca(2+) homeostasis of rods and cones. Calcium-induced calcium release (CICR) is a major contributor to steady-state and light-evoked photoreceptor Ca(2+) homeostasis in the darkness whereas store-operated Ca(2+) channels play a more significant role under sustained illumination conditions. The homeostatic response includes dynamic interactions between the plasma membrane, endoplasmic reticulum (ER), mitochondria and/or outer segment disk organelles which dynamically sequester, accumulate and release Ca(2+). Coordinated activation of SERCA transporters, ryanodine receptors (RyR), inositol triphosphate receptors (IP3Rs) and TRPC channels amplifies cytosolic voltage-operated signals but also provides a memory trace of previous exposures to light. Store-operated channels, activated by the STIM1 sensor, prevent pathological decrease in [Ca(2+)]i mediated by excessive activation of PMCA transporters in saturating light. CICR and SOCE may also modulate the transmission of afferent and efferent signals in the outer retina. Thus, Ca(2+) stores provide additional complexity, adaptability, tuneability and speed to photoreceptor signaling.